2014
DOI: 10.1242/jcs.135137
|View full text |Cite
|
Sign up to set email alerts
|

Procaspase-3 regulates fibronectin secretion and influences adhesion, migration and survival independent of catalytic function

Abstract: Caspase-3 is an effector caspase that is activated downstream of mitochondrial outer-membrane permeabilization (MOMP) during apoptosis. However, previous work has demonstrated that caspase-3-deficient mouse embryonic fibroblasts (MEFs) are resistant to mitochondrially mediated cell death and display a delay in the mitochondrial events of apoptosis, including Bax activation, MOMP and release of cytochrome c. Here, we show that caspase-3 regulates fibronectin secretion and impacts on cell morphology, adhesion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 45 publications
(47 reference statements)
2
36
0
Order By: Relevance
“…Little is known regarding FN secretion. A recent report has demonstrated that caspase 3 controls FN secretion without affecting FN1 expression [29]. The authors hypothesised that caspase 3 controls the ER-Golgi transport or vesicle trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known regarding FN secretion. A recent report has demonstrated that caspase 3 controls FN secretion without affecting FN1 expression [29]. The authors hypothesised that caspase 3 controls the ER-Golgi transport or vesicle trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, procaspase‐3, not the catalytically active form of caspase‐3, is considered to play a critical role in the appropriate maintenance of mitochondrial biogenesis. Our novel discovery of the role of procaspase‐3 in mitochondrial biogenesis further suggests the expansive roles of caspases other than in cell death, including the other non‐apoptotic roles of caspase‐3 in cell differentiation [Ishizaki et al, ; Fernando et al, ; Miura et al, ; Okuyama et al, Fujita et al, ] and regulation of cell morphology, adhesion and migration [Brentnall et al, ], and other non‐apoptotic functions [Shalini et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that FN overexpression accounts for normal epithelial senescence caused by various types of stresses [118][119][120][121][122][123] is substantially supported by the findings that silencing FN transcription or depleting periFN of pre-cancerous cells or pre-malignant tumor cells promotes characteristics of tumor progression, including proliferation, migration/invasion, tumor sizes, anchorage-independent cell growth, and angiogenesis [53,[64][65][66][67]106,[124][125][126][127]. Whether the promotion of tumor malignancy by FN depletion is due to the suppression of senescent phenotypes warrants further investigation.…”
Section: The Role Of Fn Expression In Epithelial Cell Senescence and mentioning
confidence: 99%